USE OF GLOBAL METHOD (GANZE METHOD) IN IMPROVING LANGUAGE STRUCTURE - Faizatul Widat; Laili Afrida, Nurul (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This research discusses the poor ability to manage word structures, the low learning outcomes in class II at MI Ihyaul Islam, including when speaking Indonesian, they tend to stutter and when reading they still stutter. In this research. aims to describe the use of the global method (ganze method) in improving language structure in second grade students at MI Ihyaul Islam. This research uses a qualitative approach with a field research type. The data collection technique in this research uses three types of data collection, namely, field observation, interviews and documentation. The research results show that before implementing the global method, students were less fluent in vocabulary or speaking, but after implementing the global method, students found it easier to manage language structures using series of picture media. The results of the research show that there is an increase in the global method (ganze methot), including students being good at managing word structures and teachers getting learning results that meet expectations.